Problems Existing in The Management of Coal Mine Safety Production Under The New Situation and Solutions - Nan, Yakun (International Journal of Natural Resources and Environmental Studies, 2024)
Four major coal mine accidents, for example, one of coal mine safety production management problems and way to tackle, based on the analysis of the current trend of the development of coal industry in China, on the basis of the objective factors and subjective factors of lead to safety hazard analysis, and the problems existing in the safety management and safety management measures are summarized, do management concept, technology, equipment, creative corporate culture and so on.